Factors affecting income stability of elderlies in Malaysia: The potential of reverse mortgage and the willingness to accept reverse mortgage - Lee, Chin Yee (2022)
With Malaysia's aging population, income stability for the elderly is critical to pay for their retirement expenses. However, most Malaysians do not have sufficient retirement savings in EPF. Thus, it is important to examine the income stability of the elderly to understand their financial status in retirement. To understand the demand side, this study will examine the willingness to take up a reverse mortgage from the homeowner’s perspective by employing a cross-sectional design and applied; This study examines the determinants of income stability of the elderlies and the feasibility of reverse mortgage as income replacement. To tackle income stability, house price is studied as income replacement to understand the feasibility of implementing reverse mortgage in Malaysia to overcome income instability. Data were analysed using Autoregressive Distributed Lag Model (ARDL). Employees Provident Fund (EPF) and House Price Index are the dependent variables which Household income per capital (GDP), unemployment rate, dependency ratio, total aging population and interest rate are the independent variables. The time series of this study covers from 1999 to 2019. The results reveal that all independent variables are significant in determining income stability and house price index (as an indicator of a reverse mortgage). Furthermore, there is a significant relationship between the type of primarily residential property and marital status, affordability to pay daily expenses in retirement, gender and marital status, intention to stay at the primary residential property until death, and marital status and education level. Financial institutions and policymakers should consider the importance of property ownership in delivering similar functions like EPF. The reverse mortgage is one of the related financial packages in which the elderly can use their property to exchange cash for their retirement living expenses. As a result, reverse mortgages can be a viable alternative source of income for the elderly to maintain their financial stability